(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The article examines the legal implications of overbooking, which is nothing more than the sale of tickets in a number greater than the quantity of existing seats. The practice is considered legal, but it is necessary to analyze the extent to which this event is just morally wrong and when spills the ball from the mere unpleasantness and ends up causing harm to moral and material for the passenger, which is achieved by the event in comment, and that therefore shall be entitled to require in court a repair of his consumer right injured, by means of civil liability in air transport. Thus, the research will be through the doctrine, legislation, jurisprudence and also the study of case related to the subject matter, with the goal of making not only a legal analysis of the overbooking, but also study your social and economical aspect, and so, try to formulate proposals for which the conflicts arising from the said procedure can be resolved in a more dynamic.